ANALYSIS OF TUBERCULOSIS FAMILY NURSING CARE WITH THE APPLICATION OF EFFECTIVE COUGH AND CHEST PHYSIOTHERAPY TO OVERCOME IN AFFECTIVE RESPIRATORY CLEAR IN BANYU URIP SURABAYA - Setiadi, Nanang Nurrachmat; Rusdianingseh; Hatmanti, Nety Mawarda; Zahroh, Chilyatiz (Universitas Nahdlatul Ulama Surabaya, 2023)
Background: In tuberculosis, excessive secretion production can cause airway obstruction, resulting in the problem of ineffective airway clearance. One of the nursing interventions that can be applied to clear sputum in the airways is chest physiotherapy and effective coughing techniques. Effective cough techniques and chest physiotherapy to make things easier expelling sputum so that the breathing process can run well so that it meets the body's oxygen needs. Objective: The aim of the research was to determine the application of effective coughing and chest physiotherapy to reduce the ineffectiveness of airway clearance in tuberculosis clients carried out independently. Methods: This research method uses a descriptive method with a case study approach. The instrument used is an observation sheet. The number of respondents included one tuberculosis family with a nursing diagnosis of ineffective airway clearance. Result: The results of applying effective cough techniques and chest physiotherapy given twice per day for three days with a duration of 10 to 15 minutes for each appointment showed that complaints of coughing and shortness of breath were reduced and it was easier to expel phlegm. Conclusion: The application of effective coughing techniques and chest physiotherapy has proven effective in reducing ineffective airway clearance in tuberculosis clients. Effective cough techniques and chest physiotherapy can be used as alternative measures to overcome ineffective airway clearance.